Effect of Brivaracetam on Efficacy and Tolerability in Patients With Brain Tumor-Related Epilepsy: A Retrospective Multicenter Study - Maschio, Marta; Maialetti, Andrea; Mocellini, Cristina; Domina, Elisabetta; Pauletto, Giada; Costa, Cinzia; Mascia, Addolorata; Romoli, Michele; Giannarelli, Diana (Frontiers in Neurology, 2020)
Background: epilepsy is a common symptom of brain tumors and is often pharmacoresistent.Among new antiseizure medications(ASMs)Brivaracetam(BRV)has been approved as adjunctive treatment for focal seizures and it was tested in non-oncological patient populations.This is the first study that retrospectively explored efficacy and tolerability of BRV as add-on therapy in brain tumor-related epilepsy(BTRE)patients. Material and Methods: we reviewed medical records of 33 BTRE patients from six Italian epilepsy centres;charts included:tumor history,diagnosis of BTRE,BRV added as first or second add-on for uncontrolled seizures and/or adverse events (AEs) of the previous ASMs,at least 1-month follow-up,seizure frequency and AEs assessment. Results: Thirty-three patients (19 males, mean age: 57.6 years; 14 females, mean age: 42.4 years): 11 low grade gliomas, 5 high grade gliomas, 6 meningiomas, 10 glioblastomas, 1 primary cerebral lymphoma. Fourteen patients had focal aware seizures, 9 focal unaware, 7 focal to bilateral tonic-clonic seizures, 3 patients presented more than one seizure type: focal unaware with focal to bilateral tonic clonic seizures(2 patients)and focal aware and unaware seizures(1 patient). Mean seizure frequency in the month preceding BRV introduction: 7.0; at last follow-up: 2.0 (p = 0.001). Seven patients (21.2%) reported AEs(anxiety, agitation, fatigue, vertigo)and 3 of them(9.0%)required drug withdrawal due to psychiatric adverse events(PAEs).Three other patients withdrew BRV: 1 for scarce compliance (3.0%), 2 for uncontrolled seizures(6.0%). Conclusion: our results showed that BRV could be a new therapeutic option effective in reducing seizures in BTRE patients, taking into account the incidence of PAEs in this particular population. Future and larger prospective studies are needed.